Microbiological, genomic and transcriptomic analyses of human tuberculosis lung cavities - Lenders, Laura Mary (Division of Pulmonology, 2017)
BACKGROUND: Tuberculosis (TB) remains out of control globally. Recent promising vaccine candidates have failed in clinical trials and host immunity in the lung remains poorly understood. Pathogenesis of pulmonary cavitation, the basis of TB transmission, is poorly understood. The degree of heteroresistance in the human lung remains unclear. METHODOLOGY: Multi- and extensively drug-resistant TB (MDR- and XDR-TB) patients scheduled for therapeutic lung resection surgery in Cape Town were prospectively recruited. Biopsies were obtained from specific positions in and around cavities. Drug-susceptibility testing, strain-type determination, whole-genome sequencing, and whole-transcriptome shotgun sequencing was conducted. RESULTS: Samples were obtained from 2 MDR-TB, 1 pre-XDR-TB and 12 XDR-TB patients, and 10 non- TB controls. There was considerable heterogeneity between sputum and the cavity with respect to genomic and phenotypic profiles of several drugs including ethambutol, moxifloxacin and paraaminosalicylic acid. An anatomically distinct whole-transcriptome-based pathophysiological map of TB cavities was constructed. RNA sequence reads, of which 31% were splice variants, mapped to 19,049 annotated human genes. In peri-cavitary normal-appearing tissue only 33% of pathways showed significant expression change, despite having a similar bacillary burden to diseased tissue. However, in the cavity wall 72% of pathways showed high-intensity increased expression. By contrast, in the cavity center with a high bacillary burden, 53% of these pathways were massively downregulated, differing from airways and sputum. In particular, several neuroendocrine pathways (dopamine, glutamate, synaptic long-term signalling) were significantly downregulated together with those encoding for calcium, retinoic acid-inducible gene-1, and other pathogen-recognition receptors. However, genes encoding for eukaryotic initiation factor-2, triggering receptor expressed on myeloid cell-1 and peroxisome proliferator activated receptor gamma-signalling, amongst others, were upregulated. CONCLUSION: Heterogeneity in genomic and phenotypic profiles within different parts of the cavity and sputum suggests dynamic responses of mycobacterial populations, likely, under the selective pressure of treatment, which has implications for the interpretation and development of TB-specific diagnostic tests. These data may also have important implications for understanding the pathogenesis of failed host immunity and have uncovered several, hitherto, unrecognized pathways and targets that may be useful for the design of vaccines, host-directed therapies, and transmission prevention.